Pyrazolyl Pd(II) complexes containing triphenylphosphine: Synthesis and antimycobacterial activity - Da Silva, Cristiana [UNESP]; Ribeiro, Leonardo B. [UNESP]; Furuno, Caio C. [UNESP]; Da Cunha, Gislaine A. [UNESP]; De Souza, Ronan F.F. [UNESP]; Netto, Adelino V.G. [UNESP]; Mauro, Antonio E. [UNESP]; Frem, Regina C.G. [UNESP]; Fernandes, José A.; Almeida Paz, Filipe A.; Marino, Leonardo B. [UNESP]; Pavan, Fernando R. [UNESP]; et al. (Elsevier, 2015)
Abstract Complexes of the type trans-[PdCl2(HL)(PPh3)], where HL = pyrazole (1); 3,5-dimethylpyrazole (2); 4-nitropyrazole (3); 4-iodopyrazole (4) and PPh3 = triphenylphosphine, were synthesized and characterized by elemental analyses, infrared and 1H NMR spectroscopies. Single-crystal X-ray diffraction determination on 3·0.9 CHCl3 and 4 showed that the coordination geometry around Pd(II) is nearly square-planar, with the chloro ligands in a trans configuration. In vitro antimycobacterial evaluation demonstrated that compound 4 displayed a minimum inhibitory concentration (MIC) of 7.61 ± 2.18 μM, being superior to the values observed for some commonly used antituberculosis drugs and other metal-based complexes.
Keywords: Mycobacterium tuberculosis; Pd(II) compounds; Pyrazoles; Spectroscopy; Triphenylphosphine